Anti-continuum approach on odd solitons in binary discrete media with cubic-quintic nonlinearity - Taib, L. A.; Hadi, Morteza S.A.; Umarov, Bakhram A. (IOP Publishing Ltd., 2017)
The existence and stability of bright odd strongly localized modes in discrete binary media with cubic and quintic nonlinearities are investigated mainly by applying anti-continuum method. There are three different types of bright localized modes being studied; symmetric, antisymmetric and shifted odd modes. However, certain analytical analysis is carried out first applying the anti-continuum limit assumption to estimate initial excitations in the media. It can be deduced that, the quintic nonlinearity is a significant factor for stability in antisymmetric and shifted odd modes.